Hematopoietic stem cell development in the placenta - Gekas, Christos (Int J Dev Biol, 2010)
The placenta is a highly vascularized organ that mediates fetal-maternal exchange during pregnancy and is thereby vital for the survival and growth of the developing embryo. In addition to this well-established role, the placenta was recently unveiled as a major fetal hematopoietic organ. The placenta is unique among other fetal hematopoietic organs as it is capable of both generating HSCs/progenitors de novo and establishing a major HSC pool in the conceptus while protecting HSCs from premature differentiation. The mouse placenta contains two distinct vascular regions that support hematopoiesis: the large vessels in the chorionic plate where HSCs/progenitors emerge and the labyrinth vasculature where nascent HSCs/progenitors colonize for expansion and possible functional maturation. Defining how this cytokine- and growth factor rich organ supports HSC generation, maturation and expansion may ultimately help to establish culture protocols for HSC expansion or de novo generation from pluripotent cells.